Structural evolution and magnetic properties of anionic clusters Cr2Gen (n = 3–14): photoelectron spectroscopy and density functional theory computation. (26th July 2018) - Liang, Xiaoqing; Kong, Xiangyu; Lu, Sheng-Jie; Huang, Yingying; Zhao, Jijun; Xu, Hong-Guang; Zheng, Weijun; Zeng, Xiao Cheng
Abstract: The structural, electronic and magnetic properties of dual Cr atoms doped germanium anionic clusters, ( n = 3–14), have been investigated by using photoelectron spectroscopy in combination with density-functional theory calculations. The low-lying structures of are determined by DFT based genetic algorithm optimization. For with n ⩽ 8, the structures are bipyramid-based geometries, while cluster has an opening cage-like structure, and the half-encapsulated structure is gradually covered by the additional Ge atoms to form closed-cage configuration with one Cr atom interior for n = 10 to 14. Meanwhile, the two Cr atoms in clusters tend to form a Cr–Cr bond rather than be separated. Interestingly, the magnetic moment of all the anionic clusters considered is 1 μ B . Almost all clusters exhibit antiferromagnetic Cr–Cr coupling, except for two clusters, and . To our knowledge, the cluster is the first kind of transition-metal doped semiconductor clusters that exhibit relatively stable antiferromagnetism within a wide size range. The experimental/theoretical results suggest high potential to modify the magnetic behavior of semiconductor clusters through introducing different transition-metal dopant atoms.